DNA barcoding of the Thai species of terrestrial earthworms in the genera Amynthas and Metaphire (Haplotaxida: Megascolecidae) - Ekgachai Jeratthitikul (2018)
© 2017 Terrestrial earthworms in the genera Amynthas Kinberg, 1867 and Metaphire Sims and Easton, 1972 are the most dominant and abundant earthworm species in Southeast Asia. However, the classification into species level of both genera is often confusing because of morphological similarities between species, a high level of morphological variability within species, and an absence of diagnostic characters in the juvenile stages. Therefore, similar morphological species can be erroneously lumped into a single species with several morphotypes or can be indicated as a species complex. In this study, we used a 658 bp DNA fragment of the mitochondrial cytochrome c oxidase subunit 1 gene for DNA barcoding for species identification and delimitation of terrestrial earthworms in the genera Amynthas and Metaphire collected primarily in Thailand, with additional samples from Laos and Malaysia. In total, 158 sequences from adult earthworms were investigated. Multiple DNA barcoding approaches revealed 77 candidate earthworm species (31 for Metaphire and 46 for Amynthas). Twenty-nine of these molecular operational taxonomic units, or species, corresponded with formerly described species, but the remaining were unknown species and probably new to science. The average K2P distance within species was 1%, whereas the average divergence between species was 20%, with a barcoding gap of around 5–13%, reflecting the obvious barcode gap in these animals. In addition, the possible cryptic speciation of Metaphire houlleti, Amynthas longiculicaulatus and Amynthas arenulus species complexes was supported. No morphological characters have yet been identified that can be used as diagnostic characters within these three species-complexes.